PENGARUH WARNA CAHAYA LAMPU DAN INTENSITAS CAHAYA YANG BERBEDA TERHADAP RESPONS BENIH IKAN BANDENG (Chanos – Chanos forskal) dan BENIH IKAN NILA (Oreochromis niloticus) - Sukardi, Sukardi; Yanto, Subari; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
The purpose of this research is to know the influence of light color of lamp and different light intensity against the response of milkfish seed (Chanos - chanos forskal) and tilapia fish seed (Oreochromis niloticus). This experiment with experimental design used is Completely Random Design Pattern Factorial (Factorial RAL) consisting of two variables that is light color lamp with 3 level of treatment that is: red, blue, and yellow and light intensity with 2 level of treatment that is: intensity 500 lux and 1000 lux. Research variable observed is amount Fish caught from the type of light treatment given. Examination technique used in this study is the analysis of variance that is processed using SPSS version 23. The results showed the blue light of lamp with the intensity of 500 lux most responded by milkfish seeds and granting the yellow light of lamp  with the intensity of 1000 lux most responded by the tilapia seeds in the observation time after the 15th minute